Analysis of Mathematical Beliefs of Madrasah Tsanawiyah Students After Using the Geometry Transformation Digibook - Komara; Lestari, Puji; Supratman (Mathematics Education Journal, 2024)
Mathematical belief is students' belief in mathematics which can construct their cognitive domain in the mathematics learning process. This research aims to analyze and describe students' mathematical beliefs after using the geometric transformation digibook. The subjects in this study were 32 students of class IX-B MTs Negeri 3 Ciamis. The method used in this research is descriptive qualitative method. The data collection technique in this study is through observation and a mathematical belief questionnaire. The instruments used in this research were the geometric transformation digibook and the mathematical belief questionnaire. Based on the results of the study and discussion, it can be concluded that after learning mathematics using the geometric transformation digibook, students' mathematical beliefs in each of the main dimensions of mathematical belief, namely: about mathematics education are in the high category, about themselves are in the high category and about the social context are in the high category.